Isotonicity of the metric projection with applications to variational inequalities and fixed point theory in Banach spaces - Kong, Dezhou; Liu, Lishan; Wu, Yong Hong (2016)
© 2016 Springer International PublishingIn this paper, we discuss isotonicity characterizations of the metric projection operator, including its necessary and sufficient conditions for isotonicity onto sublattices in Banach spaces. Then, we demonstrate their applications to variational inequalities and fixed point theory in Banach spaces. Our work generalizes many existing results obtained in earlier work.